Subject-specific biomechanics influences tendon strains in patients with Achilles tendinopathy - Alessia Funaro; Vickie Shim; Ine Mylle; Benedicte Vanwanseele (Scientific Reports)
Abstract The treatment of Achilles tendinopathy is challenging, as 40% of patients do not respond to existing rehabilitation protocols. These protocols neglect individual Achilles tendon (AT) characteristics, which are crucial for healing of the tendon tissue. Although prior studies suggest an optimal strain for AT regeneration (6% tendon strains), it is unclear if current protocols meet this condition. Our study aimed to analyse the impact of a selection of rehabilitation exercises on tendon strains in patients with Achilles tendinopathy, using subject-specific finite element (FE) models of the free AT. Second, this study aimed to explain the influence of muscle forces and material properties on AT strains. The 21 FE models of the AT included the following subject-specific features: geometry estimated from 3D freehand ultrasound images, Elastic modulus estimated from the experimental stress‒strain curve, and muscle forces estimated using a combination of 3D motion capture and musculoskeletal modelling. Exercises were ranked based on strain progression, starting from concentric and eccentric exercises, and going to more functional exercises, which impose a greater load on the AT. There was no significant difference between the unilateral heel drop and walking, and both exercises fell within the optimal strain range. However, when examining individual strains, it became evident that there was diversity in exercise rankings among participants, as well as exercises falling within the optimal strain range. Muscle forces notably affected strains more than material properties. Our findings indicate the importance of tailored rehabilitation protocols that account for individual morphological, material, and muscle characteristics.